Effects of a phagocytosis-stimulating factor on the phagocytic process of polymorphonuclear neutrophils. - Ishibashi, Y (1982)
The effect of phagocytosis-stimulating factor (PSF) on phagocytosis was studied in detail. PSF did not affect the Fc receptor-mediated phagocytosis, whereas PSF enhanced the ingestion step, but not attachment step, of C3b receptor-mediated phagocytosis by polymorphonuclear neutrophils (PMNs), suggesting that PSF may specifically modulate the C3b receptor function of PMNs. PSF generated from guinea pig PMNs enhanced phagocytosis by rabbit PMNs, and rabbit PMN-produced PSF accelerated the phagocytosis by guinea pig PMNs, indicating that PSF is not specific for animal species. The effects of PSF on some PMN functions, such as O2- generation, chemotaxis, adherence, and enzyme release, were also studied. Only O2- generation from PMNs was significantly increased in the initial phase of phagocytosis, and this stimulation of O2- generation was completely parallel with the stimulation of phagocytosis by PSF. Resting PMNs hardly generated the superoxide anions by PSF treatment, suggesting that PSF does not affect the O2- forming system directly.